Acaricidal and larvicidal activity of Piper marginatum and Piper tuberculatum essential oils from Ecuador - Moncayo-Baño, Shirley Madeleine; Rondón-Rivas, María Eugenia; Cornejo-Sotomayor, Francisco Xavier (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2024)
Piper marginatum and Piper tuberculatum are species used by local indigenous, people who live especially in eastern Ecuador, for their insecticidal properties. This study aimed to determine the acaricidal and larvicidal activity of the essential oil of these species. The essential oils were obtained by hydrodistillation. The acaricidal activity was evaluated with the contact toxicity method against larvae of the tick Rhipicephalus microplus. Larvicidal activity was determined against Aedes aegypti mosquito larvae following WHO recommended guidelines. The essential oils of P. marginatum and P. tuberculatum showed an acaricidal potential with LC50 of 0.90 and 0.73 µL mL-1, respectively. In addition, excellent larvicidal activity was obtained with LC50 of 11.87 µL mL-1 (P. marginatum) and 8.42 µL mL-1 (P. tuberculatum) at 48 hours of evaluation. This is the first report of the acaricidal activity of P. marginatum and P. tuberculatum essential oils against Rhipicephalus microplus tick larvae. The results indicate that essential oils could be a natural alternative for the controlling these pests and would justify their ethnobotanical applications as a lice and tick repellent.